The Grammar Translation Method in Teaching Structure and Written Expression of TOEFL ITP: Is It Still Effective in Today Era? - Prasetya, Angga Eka; Asyhar , Wildan Isna; Muchyidin , M Syaichul (Institut Agama Islam Negeri Madura, 2024)
The grammar translation method (GTM) is an